2019
DOI: 10.5553/tvc/0165182x2019061001001
|View full text |Cite
|
Sign up to set email alerts
|

De psychische gezondheid van gedetineerden in België en Nederland: een systematisch overzicht

Abstract: Internationaal onderzoek toont consistent aan dat psychische gezondheidsproblemen (psychiatrische stoornissen, psychische klachten en middelengebruik) disproportioneel vaker voorkomen bij gedetineerden in vergelijking met de algemene bevolking. Een slechte psychische gezondheid gaat gepaard met verschillende ongunstige uitkomsten, waaronder suïcide. In de afgelopen jaren werden veel nieuwe Belgische en Nederlandse gegevens over dit thema gepubliceerd in de wetenschappelijke literatuur, die tot op heden niet we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
2
14
0
1
Order By: Relevance
“…This study is one of the few to delineate factors associated with suicide attempts among prisoners with suicidal ideation, thereby helping us to better understand the transition from ideation to action in an understudied population at high risk for suicide. A noteworthy strength of the study is its large sample (n = 1326), representing 13.5% of the average daily prisoner population in Belgium (N = 9835), which was broadly representative of the annual census data during the study period (Favril and Dirkzwager, 2019). Six methodological limitations should however be borne in mind when…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study is one of the few to delineate factors associated with suicide attempts among prisoners with suicidal ideation, thereby helping us to better understand the transition from ideation to action in an understudied population at high risk for suicide. A noteworthy strength of the study is its large sample (n = 1326), representing 13.5% of the average daily prisoner population in Belgium (N = 9835), which was broadly representative of the annual census data during the study period (Favril and Dirkzwager, 2019). Six methodological limitations should however be borne in mind when…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In order to identify such high-risk groups who might benefit from targeted interventions, screening instruments should therefore, amongst others, incorporate questions about these clinical variables (Marzano et al, 2016;Brown et al, 2017;Gould et al, 2018). Although of interest, however, reliance on such factors may be of limited practical use for identifying suicidal prisoners prone to behavioural enaction, owing to their overall high prevalence in mainstream prisoner populations (Fazel et al, 2016;Favril and Dirkzwager, 2019). Therefore, guided by specific constructs from the Research Domain Criteria (Glenn et al, 2018), future research should focus on novel volitional factors implicated in the transition from ideation to action, and test the predictive validity of screening instruments incorporating such factors.…”
Section: Clinical and Research Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding imported characteristics of inmates, research has found that females are more vulnerable than males for several reasons (Favril & Dirkzwager, 2019; Granja, da Cunha, & Machado, 2015; Mollard & Brage Hudson, 2016). They appear to be more socio-economically deprived (Lewis, 2006; Mollard & Brage Hudson, 2016; Moloney, van den Bergh, & Moller, 2009; Owen & Bloom, 1995), which has sometimes led to their involvement in drug-related crimes (Bloom, Owen, & Covington, 2012; Carson, 2018; Joosen et al, 2016) or property crimes (Bloom et al, 2012; Kestermann, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Psychiatric disorders are more prevalent among prison inmates than among the general population (Hanssens, Vyncke, Steenberghs, & Willems, 2018; James & Glaze, 2006; Mallicoat, 2012; Plugge, Douglas, & Fitzpatrick, 2011). Moreover, several studies have found that female inmates are more likely than male inmates to have psychiatric disorders and to misuse substances (Belknap, Lynch, & DeHart, 2016; Bronson & Berzofsky, 2017; Favril & Dirkzwager, 2019; Favril, Vander Laenen, & Audenaert, 2017; Gunter et al, 2012; James & Glaze, 2006; Steadman, Osher, Robbins, Case, & Samuels, 2009; Van den Bergh, Gatherer, Fraser, & Moller, 2011).…”
Section: Introductionmentioning
confidence: 99%